Motivation as key factor of deploying lean technologies in medical institutions (an analytic review) - E. A. Perevezentsev; V. M. Levanov (Кубанский научный медицинский вестник, 2020)
Aim. To assess the importance, role, methods and conditions for creating and sustaining positive motivation of medical personnel in deploying a modern management system based on lean production to optimise the production ﬂow in medical institutions, improve quality, availability and efﬁciency of public medical care.Materials and methods. The authors employed historical, bibliometric and statistical methods to analyse domestic and foreign scientiﬁc archives on lean production, motivation and motivational risks as key factors in implementing lean technologies in medical institutions.Results. Implementation of lean production (LP) as a manufacturing management system is among key conditions for creating a new model of the medical institution. Principles of LP are applied at three interfaces: with patients, personnel and resources. Positive motivation of employees is prerequisite for accomplishing a project, which requires supervisors to know and leverage the basics of motivational management. Creation of a motivating environment for various categories of employees in developing a LP system requires taking into account the type and management culture level of a medical institution.Conclusion. In order to create and sustain motivation for realising creative potential of the team, it is necessary to account for the motivation risks, develop and implement a motivation system differentially by employee categories and project stages. Effective motivational measures are necessarily based on a system of material and non-material incentives with clear and achievable criteria, amounts and forms valued by employees and rooted in medical and economic feedback of implementing the LP principles.